Ecological engineering design : restoring and conserving ecosystem services - Matlock, Marty D.; Morgan, Robert A. (Hoboken, NJ : Wiley, 2011)
'Ecologically-sensitive building and landscape design is a broad, intrinsically interdisciplinary field. Existing books independently cover narrow aspects of ecological design in depth (hydrology, ecosystems, soils, flora and fauna, etc.), but none of these books can boast of the integrated approach taken by this one. Drawing on the experience of the authors, this book begins to define explicit design methods for integrating consideration of ecosystem processes and services into every facet of land use design, management, and policy. The approach is to provide a prescriptive approach to ecosystem design based upon ecological engineering principles and practices. This book will include a novel collection of design methods for the non-built and built environments, linking landscape design explicitly to ecosystem services'--
'Ecologically-sensitive building and landscape design is a broad, intrinsically interdisciplinary field'--
Includes bibliographical references and index.
Keywords: Ecological engineering; Sustainable design; Environmental engineering